THE EFFECTS OF READING HABITAND VOCABULARY MASTERYTOWARDS HORTATORY EXPOSITION WRITING SKILL - Fitri Senny Hapsari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Abstract: The purpose on this research is to know whether there are significant effects ofreading habit and vocabulary mastery hortatory exposition writing skill.The research wasconducted at SMAN102 and SMAN 89 of the eleventh grade with the total population of 390students and the sample was 80 students that were randomly taken. The method used in theresearch was a survey. Data of reading habit, vocabulary mastery and hortatory expositionwriting skill were collected from a test. The data was analysed using descriptive statisticalmethod, multiple correlation coefficient, determination coefficient, and multiple regressionanalysis. Ftest and ttestwere analyzed.Data collection done by giving essay test for hortatoryexposition writing skill, thirty (30) items of multiplechoice test for Reading Habit, and twenty(20)items of multiplechoice test for vocabulary mastery given to the subjects at SMAN 102and SMAN 89.The result of data analyzes shows that there are significant effects of readinghabitandvocabulary mastery towards hortatoryexposition writing skill.Keywords: Reading Habit, Vocabulary Mastery, and Hortatory Exposition Writing Skill.